2019
DOI: 10.1002/rmb2.12271
|View full text |Cite
|
Sign up to set email alerts
|

Performance of anti‐Müllerian hormone (AMH) levels measured by Beckman Coulter Access AMH assay to predict oocyte yield following controlled ovarian stimulation for in vitro fertilization

Abstract: Purpose We evaluated the performance of anti‐Müllerian hormone (AMH) measured by the Beckman Coulter fully automated Access assay to predict oocyte yield following controlled ovarian stimulation (COS) for in vitro fertilization (IVF). Methods The correlation between the Access assay and the pre‐mixing method with Generation II ELISA assay (Gen II pre‐mix assay) was assessed using 230 blood samples. The relationship of AMH level measured by the Access assay and the actual number of oocytes retrieved following C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Analysis ROC revealed that AMH and women's age are the most accurate of other tests in predicting ovarian response compared to the basal level of FSH. The AUC for AMH was higher than age and basal FSH, and these findings match with previous studies [35,36]. In contrast, a previous study found the antral follicle count (AFC) to be better than the AMH level [37].…”
Section: Discussionsupporting
confidence: 89%
“…Analysis ROC revealed that AMH and women's age are the most accurate of other tests in predicting ovarian response compared to the basal level of FSH. The AUC for AMH was higher than age and basal FSH, and these findings match with previous studies [35,36]. In contrast, a previous study found the antral follicle count (AFC) to be better than the AMH level [37].…”
Section: Discussionsupporting
confidence: 89%
“…Usually, basal serum FSH level at day 3 was used to predict ovarian reserve, and level >10 IU/liter was considered consistent with poor ovarian response. However, compared with AMH, basal serum FSH was not independently associated with ovarian response, NOR, and GQE [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AMH has been used to assess ovarian reserve parameters and response to gonadotrophin stimulation, reproductive outcomes of infertile women [ 4 , 7 10 ]. AMH is an emerging and one of the strongest markers of NOR during IVF cycles [ 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, fully automated AMH assays were released by Beckman Coulter (Access) and by Roche (Elecsys) [14,15]. The automated assay uses recombinant AMH as a calibrator, thereby reducing the test time and improving sample instability or variability.…”
Section: Introductionmentioning
confidence: 99%